Feasibility and Functional Outcome of Robotic Assisted Kidney Transplantation Using Grafts With Multiple Vessels: Comparison to Propensity Matched Contemporary Open Kidney Transplants Cohort - Nataraj, Sachin Arakere; Zafar, Feroz Amir; Ghosh, Prasun; Ahlawat, Rajesh (Frontiers in Surgery, 2020)
Introduction The aim of the study was to report the perioperative and functional results of Robotic assisted kidney transplantation (RAKT) in Grafts with multiple vessels (GMVs) and compare it to the results of Open kidney transplantation (OKT) with GMVs Materials and Methods Patients undergoing RAKT from living donors using GMVs were reviewed from prospectively collected RAKT database at our institution between March 2013 and March 2018. Patient undergoing Open kidney transplantation (OKT) using GMVs served as controls. Ex-Vivo bench surgical reconstruction of GMVs was done according to specific anatomy. Propensity score matching was used to balance the sample size in the two groups. Results Of 153 RAKT and OKT procedures, 86 cases were eligible for propensity score matching for the statistically significant variables (standardized difference > 0.10) and 43 procedures were assigned to each group. Median anastomoses, total and cold ischemia and rewarming times did not differ significantly between the RAKT and OKT groups. In comparison with OKT in GMVs we found that RAKT with GMVs had less pain score on post op 2nd day(p=0.03). There was also a significant difference in mean analgesic requirement(p=0.02), hospital stay(p=0.05) and incision length(p=0.04). Most of the major, minor surgical, and medical postoperative complications were comparable between the two groups except for wound related events(p=0.002). Conclusion Multiplicity of renal vessels in RAKT does not adversely affect patient or graft survival compared with the OKT. Satisfactory functional outcome can be achieved by RAKT similar to OKT in GMVs. RAKT seems to have advantage over OKT in that it is less invasive and has the potential to cause fewer low grade complications. Small sample size and short follow-up are the main limitations of the study.